Comportamento tribológico de poliuretanos elastoméricos no desgaste por deslizamento contra capa de poliamida 11 de dutos flexíveis - Bertholdi, Jonas (2016)
In this work small and large-scale wear tests of polyurethane (PU) sliding against polyamide (PA) were carried out. In the large-scale tests, PU and PA samples were submitted to conditions similar to those found in oil and gas platform operations. The wear of these samples was measured using a coordinate measuring machine. Using the small-scale test configuration, the influence of contact geometry, sliding velocity, sliding stroke and contact pressure at the coefficient of friction (COF) and on the wear mechanisms was evaluated. In both test scales, the wear mechanisms of PA and PU samples were analyzed using a scanning electron microscope. The thermal behavior of PA samples was investigated using differential scanning calorimetry. The PA physic-chemical analysis was performed using X-ray diffraction and Raman spectroscopy and infrared spectroscopy for PU. In large-scale tests was observed that the outer cover of flexible riser pipes had a maximum wear rate of 0.016 mm/km, while in the liner this wear rate was 0.264 mm/km. It was also observed that variations in the hardness of PU liner lead to an important change on the wear mechanisms and, consequently, on the wear rate. The wear rate at large-scale was also strongly affected by the contact temperature. Due to the reduction of the contact temperature, a sharp reduction on the liner wear rate was observed. However, no significant variation in the rate of wear of PA riser cover was noticed. In small-scales tests, under the same sliding velocity and contact pressure observed in the field, the tribological wear behavior was changed. It was also observed that increasing the contact pressure or reducing the sliding stroke leads to a decrease the COF, while the sliding velocity only induced a change in this parameter if the contact temperature was significantly increased. Using test parameters in small scale which lead to a temperature rise in the tribocontact, it was possible to reproduce the tribological behavior observed in large-scale test.